Self-powered Users, “Free” Energy Harvesting and Interaction-powered Devices: a Hybrid Vision for Improved Sustainability - José Luís Silva / José L. Silva / J. L. Silva (ACM Conference on Human Factors in Computing Systems, 2020)
In a world facing climate change emergency, energy harvesting must be improved. Future interactive devices (with new materials) and a move of energy harvesting from devices to users can trigger this improvement. This paper presents a vision on how (many) future interactive devices should be powered. Beyond the benefits of a self-powered and ultra-low power interactive devices vision, a complementary one with self-powered users and “free” energy harvesting is essential. For example, harvesting user’s energy (e.g. heart rate pulsations) and/or enabling him/her to produce (e.g. kinetic/inertial energy harvesting) and store (e.g. wearables) energy for future interactions. Self-powered users can then perform interactions with devices (that require only power during interaction or extra power during interaction) powering them through direct contact interaction. This will allow the removal of built-in batteries on these devices and a global reduction of batteries. The proposed hybrid vision combines self-powered devices/users and “free” energy harvesting.